Molecular analysis of the Sydney rock oyster (Saccostrea glomerata) CO2 stress response - Ertl, Nicole G; O'Connor, W A; Wiegand, A; Elizur, A (Climate Change Responses, 2016)
Background: Human activities have led to a substantial increase in carbon dioxide (CO2) emission, with further increases predicted. A RNA-Seq study on adult Saccostrea glomerata was carried out to examine the molecular response of this bivalve species to elevated pCO2. Results: A total of 1626 S. glomerata transcripts were found to be differentially expressed in oysters exposed to elevated pCO2 when compared to control oysters. These transcripts cover a range of functions, from immunity (e.g. pattern recognition receptors, antimicrobial peptides), to respiration (e.g. antioxidants, mitochondrial respiratory chain proteins) and biomineralisation (e.g. carbonic anhydrase). Overall, elevated levels of CO2 appear to have resulted in a priming of the immune system and in producing countermeasures to potential oxidative stress. CO2 exposure also seems to have resulted in an increase in the expression of proteins involved in protein synthesis, whereas transcripts putatively coding for proteins with a role in cilia and flagella function were down-regulated in response to the stressor. In addition, while some of the transcripts related to biomineralisation were up-regulated (e.g. carbonic anhydrase 2, alkaline phosphatase), a small group was down-regulated (e.g. perlucin). Conclusions: This study highlighted the complex molecular response of the bivalve S. glomerata to expected near-future ocean acidification levels. While there are indications that the oyster attempted to adapt to the stressor, gauged by immune system priming and the increase in protein synthesis, some processes such cilia function appear to have been negatively affected by the elevated levels of CO2.